As Mídias sociais como estratégia de marketing na difusão documental do Arquivo Nacional - GRANGEIRO, Gilead (2022)
The use of social media as a marketing strategy for the documentary diffusion is the object of study of this Work of conclusion of course, highlighting its importance in the social context where more and more people use these tools to satisfy their informational needs, because they are always available when they need it. The technology made it possible for information professionals to use these tools to work with the marketing of the document custodian institutions and to give visibility to the actions developed to make information available to all types of users who need them. In order to reach the proposed objectives, a bibliographical research was used with the help of a questionnaire applied to the professionals of the National Archives who work with diffusion and access and from the analysis of the data it was possible to verify that the social media allied to the diffusion process brought results satisfactory for the marketing of the institution.